2016
DOI: 10.13168/cs.2016.0053
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF K₂O AND MgO ON THE FORMATION AND HYDRATION ACTIVITY OF Ba-BEARING CALCIUM SULFOALUMINATE

Abstract: Ba-bearing calcium sulfoaluminate (C 2.75

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The A 2 Ni(Pd) 3 Ch 4 compounds are all highly insulating with a band gap of about 1 eV. [40,42,[44][45][46]48] Because the divalent nickel and palladium cations manifest a low spin configuration 3d 8 with S being 0, they in general demonstrate weak diamagnetic or paramagnetic signal. [46] However, it was reported that the Rb 2 Ni 3 S 4 specimens have a small residual ferromagnetic moment if they were soaked in water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A 2 Ni(Pd) 3 Ch 4 compounds are all highly insulating with a band gap of about 1 eV. [40,42,[44][45][46]48] Because the divalent nickel and palladium cations manifest a low spin configuration 3d 8 with S being 0, they in general demonstrate weak diamagnetic or paramagnetic signal. [46] However, it was reported that the Rb 2 Ni 3 S 4 specimens have a small residual ferromagnetic moment if they were soaked in water.…”
Section: Introductionmentioning
confidence: 99%
“…[46] However, it was reported that the Rb 2 Ni 3 S 4 specimens have a small residual ferromagnetic moment if they were soaked in water. [48] This unexpected ferromagnetism was attractive because it may be related to a long-sought flat-band ferromagnetism characteristic of the kagome lattice. [49] A recent study observed metalinsulator transition and superconductivity in Rb 2 Pd 3 Se 4 under high pressure.…”
Section: Introductionmentioning
confidence: 99%